N-LITHIOMETHYL-N,N'N'N''-TETRAMETHYLDIETHYLENETRIAMINE - THE 1ST-ALKYLLITHIUM COMPOUND WHICH IS MONOMERIC IN HYDROCARBONS - Klumpp, Gerhard; Luitjes, Hendrikus; Schakel, Marius; de Kanter, Frans; Schmitz, Robert; van Eikema Hommes, Nico (Angewandte Chemie (International Edition in English), 1992)
NMR studies and MNDO calculations show that the title compound exists as two monomeric species in solution with two most stable structures (one of the structures is shown here). As expected, N2 and N3 are coordinated to the Li atom: however, the Li-N1 interaction is quite weak.